Ekonomi Islam: transaksi dan problematikanya - Athoillah, Muhammad Anton (Sekolah Tinggi Agama Islam Negeri Salatiga, 2013)
Transaction in Islam is often criticized for not having a clear differentiator from the other transaction.Although departing from the different basic principles, but havingnot a much different impact than theother transaction. Often asked, whether Islamic economics is capitalism minus usury or socialism plusIslam? Therefore, no less important to know are, what a plus-minus of conventional transaction, whatthe distinguishing element between a conventional transaction with Shariâah transaction, and whetherthe distinguishing element has different impact than what is produced by a conventional transaction.